Consideration of explosion, fire and impact load in building structural design to mitigate disaster - Mun, Kwai Peng, Ir.; Hee, M.C., Ir. (The Institution of Engineers, Malaysia, 2013)
Link to publisher’s homepage at http://www.myiem.org